Strategic Management of Public Health Risks: Correlation Between Water Quality and Aedes Sp. in South Jakarta - Maharani, Zulfia; Saputra, Atang; Syarifuddin (APTISI Transactions on Management (ATM), 2024)
This study focuses on investigating the relationship between water temperature, water pH, and residual water chlorine with the presence of Aedes sp. larvae in the RW 06 area of North Gandaria Village, Kebayoran Baru District, South Jakarta. Utilizing an analytical cross-sectional research design, the study encompasses a population of 667 houses in RW 06, with a sample size of 92 houses determined through Proportional Simple Random Sampling. The analysis employs chi-square tests to examine the associations between the variables. The findings reveal that there is no significant relationship between water temperature and the presence of Aedes sp. larvae (P-value = 0.659) and no significant relationship between water pH and the presence of Aedes sp. larvae (P-value = 0.434). However, the research does identify a noteworthy association between residual water chlorine and the presence of Aedes sp. larvae (P-value = 0.000). This emphasizes the importance of water chlorine levels in influencing the presence of Aedes sp. larvae in the specified area. The study's outcomes contribute valuable insights to the management of water quality in the context of Aedes sp. larvae control.